Phylogenetic relationships of \(Quercus\) species (Fagaceae) in Vietnam based on multiplexed inter simple sequence repeat genotyping by sequencing - Hoang Thi, Binh; Tetsukazu, Yahara; Yoshihisa, Suyama; Shuichiro, Tagane; Nguyen, Van Ngoc (Academia Journal of Biology, 2024)
Quercus is the largest genus of the family Fagaceae in the world and the second-largest in Vietnam, with approximately 50 species. However, the phylogeny study of the Quercus genus in Vietnam has yet to be thoroughly explored. In this study, we utilize the genome-wide single-nucleotide polymorphisms (SNPs) data obtained through Multiplexed Inter Simple Sequence Repeat Genotyping by sequencing (MIG-seq) to explore the phylogenetic relationships among Quercus species in Vietnam. The results of this study reveal that all Quercus species in Vietnam belong to subgenus Cerris and the phylogenetic analysis strongly supports the recognition of two infrageneric sections: Quercus and Ilex section for the Vietnamese Quercus. These results also confirm that the monophyly of Quercus in Vietnam is strongly supported by both morphological and molecular data. The results of this study also align entirely with previous research, indicating that Quercus species in Asia fall under the subgenus Cerris, comprising two sections: section Ilex and section Cyclobalanopsis.